Effect of nerve growth factor dimeric mimetic GK-2 on microcirculation in skeletal muscle on the hind limb ischemia model in rats - I. B. Tsorin; A. O. Efimova; E. S. Pekeldina; M. B. Vititnova; S. A. Kryzhanovskii (LLC "Publisher OKI", 2021)
The purpose of the study. In experiments on a hind limb ischemia model in rats, the effect of the TrkA-receptor agonist of the NGF 4th loop dimeric dipeptide mimetic compound GK-2 has been studied on microcirculation in ischemic skeletal muscle.Methods. the Hind limb ischemia was caused in white male mongrel rats by the femoral artery resection. The compound GK-2 was administered intravenously (1 mg/kg/day during 14 days). Microcirculation parameters were recorded using a computer laser analyzer "LAKK-OP2". Registration was carried out simultaneously in the intact and operated limb before the operation, 1 and 14 days after it.Results. In the conditions of the hind limb ischemia model, it was shown that the compound GK-2 almost completely restored the perfusion index and its variation coefficient in the ischemic muscle to the intact contralateral limb level by the 14th day after surgery.Conclusion. It can be assumed that the anti-ischemic effect of the compound GK-2 is associated with the restoration of microcirculation as a result of increased neoangiogenesis.